Coordinated transcription factor and promoter engineering to establish strong expression elements in Saccharomyces cerevisiae. Issue 7 (19th May 2016) - Leavitt, John M.; Tong, Alice; Tong, Joyce; Pattie, Jonathan; Alper, Hal S.
Abstract: Gene expression requires the coordination of trans‐acting factors and cis‐DNA elements to initiate transcription. Here we present a coordinated approach that combines cis‐acting element engineering with mutant trans‐acting factors to engineer yeast promoters. Specifically, we first construct a hybrid promoter based on the ARO9 upstream region that exhibits high constitutive and inducible expression with respect to exogenous tryptophan. Next, we perform protein engineering to identify a mutant Aro80p that affords both high constitutive expression while retaining inducible traits. We then use this mutant trans‐acting factor to drive expression and generate ultra‐strong promoters with transcriptional output roughly 2 fold higher than TDH3 (GPD), one of the strongest promoters to‐date. Finally, we used this element to construct a modular expression system capable of staged outputs resulting in a system with nearly 6‐fold, 12‐fold and 15‐fold expression relative to the off‐state. This work further highlights the potential of using endogenous transcription factors (including mutant factors) along with hybrid promoters to expand the yeast synthetic biology toolbox. Abstract : Gene expression requires transcription factor proteins to bind to DNA promoter elements in order to initiate transcription. In this study, the authors present a coordinated approach that engineers both transcription factor and promoter elements to achieve strong and modular yeast expression systems. This resulted in a mutant transcription factor used to drive the expression of ultra‐strong promoters and a modular expression system capable of staged outputs. This work expands the expression tools available in yeast and demonstrates the potential for engineering endogenous transcription factors and promoter elements.